Science in King Tut's tomb - Enz, Tammy (Science of history (Capstone Press), 2022)
"One of the most well-known pharaohs from ancient Egypt was King Tut. Did you know that science played a big role in ancient Egypt? Find out how the Egyptian pyramids were engineered. Learn about the science behind King Tut's mummy. And discover how modern technology helps us learn more about King Tut's life and death"--